NF-E2-Related Factor 2 (Nrf2) Ameliorates Radiation-Induced Skin Injury - Xue, Jiao; Yu, Chenxiao; Tang, Yiting; Mo, Wei; Tang, Zhicheng; Sheng, Wenjiong; Jiao, Yang; Zhu, Wei; Cao, Jianping (Frontiers in Oncology, 2021)
Radiation-induced skin injury (RISI) commonly occur in cancer patients who received radiotherapy and is one of the first clinical symptoms after suffering from nuclear exposure. Oxidative damage is the major causes of RISI. Nuclear factor erythroid 2-related factor 2 (Nrf2) is considered as a key mediator of the cellular antioxidant response. However, whether Nrf2 can alleviate RISI after high-dose irradiation remains unknown. In this study, we demonstrated that Nrf2-deficient (Nrf2-/-) mice were susceptible to high-dose irradiation and adenovirus-mediated overexpression of Nrf2 (ad-Nrf2) protected against radiation in skin cells. Overexpression of Nrf2 attenuated the severity of skin injury after high-dose electron beam irradiation. To uncover the mechanisms of Nrf2 involved in RISI, mRNA sequencing technology was performed to analyze the mRNA expression profiles of Ad-Nrf2 skin cells following radiation. The results revealed that a total of 127 genes were significantly changed, 55 genes were upregulated, and 72 genes were downregulated after Nrf2 overexpression. GSEA showed that Nrf2 was associated with positive regulation of genes involved in the reactive oxygen species pathway after radiation. Taken together, this study illustrated the role of Nrf2 in RISI and provided potentially strategies for ameliorating RISI.